The Genome-Based Metabolic Systems Engineering to Boost Levan Production in a Halophilic Bacterial Model - TOKSOY ÖNER, EBRU; ARĞA, KAZIM YALÇIN (MARY ANN LIEBERT, INC, 2018)
Metabolic systems engineering is being used to redirect microbial metabolism for the overproduction of chemicals of interest with the aim of transforming microbial hosts into cellular factories. In this study, a genome-based metabolic systems engineering approach was designed and performed to improve biopolymer biosynthesis capability of a moderately halophilic bacterium Halomonas smyrnensis AAD6(T) producing levan, which is a fructose homopolymer with many potential uses in various industries and medicine. For this purpose, the genome-scale metabolic model for AAD6(T) was used to characterize the metabolic resource allocation, specifically to design metabolic engineering strategies for engineered bacteria with enhanced levan production capability. Simulations were performed in silico to determine optimal gene knockout strategies to develop new strains with enhanced levan production capability. The majority of the gene knockout strategies emphasized the vital role of the fructose uptake mechanism, and pointed out the fructose-specific phosphotransferase system (PTSfru) as the most promising target for further metabolic engineering studies. Therefore, the PTSfru of AAD6(T) was restructured with insertional mutagenesis and triparental mating techniques to construct a novel, engineered H. smyrnensis strain, BMA14. Fermentation experiments were carried out to demonstrate the high efficiency of the mutant strain BMA14 in terms of final levan concentration, sucrose consumption rate, and sucrose conversion efficiency, when compared to the AAD6(T). The genome-based metabolic systems engineering approach presented in this study might be considered an efficient framework to redirect microbial metabolism for the overproduction of chemicals of interest, and the novel strain BMA14 might be considered a potential microbial cell factory for further studies aimed to design levan production processes with lower production costs.
Keywords: metabolic systems engineering; levan; overproduction; insertional mutagenesis; Halomonas smyrnensis; HALOMONAS SMYRNENSIS AAD6(T); MICROBIAL LEVAN; BACILLUS-AMYLOLIQUEFACIENS; BIOSYNTHESIS; LEVANSUCRASE; ELONGATA; CULTURE; ECTOINE; FRUCTOOLIGOSACCHARIDES; OPTIMIZATION